If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying F(X) = 3X + -4 + X(9X + -7) Multiply F * X FX = 3X + -4 + X(9X + -7) Reorder the terms: FX = 3X + -4 + X(-7 + 9X) FX = 3X + -4 + (-7 * X + 9X * X) FX = 3X + -4 + (-7X + 9X2) Reorder the terms: FX = -4 + 3X + -7X + 9X2 Combine like terms: 3X + -7X = -4X FX = -4 + -4X + 9X2 Solving FX = -4 + -4X + 9X2 Solving for variable 'F'. Move all terms containing F to the left, all other terms to the right. Divide each side by 'X'. F = -4X-1 + -4 + 9X Simplifying F = -4X-1 + -4 + 9X Reorder the terms: F = -4 + -4X-1 + 9X
| 3h^2-60=24h | | 9y+5x=10 | | y=11x^2+5x+13 | | 3h+9=4h-3 | | c+3=15-3c | | (x-80)/X=0.2 | | 4(2x-4)=8x+56 | | 4(2x-4)=8x+36 | | 4(2x-4)=8x+20 | | 4(2x-4)=8x+19 | | 4(2x-4)=8x+18 | | 4(2x-4)=8x+17 | | 4(2x-4)=8x+15 | | 4(2x-4)=8x+14 | | 4(2x-4)=8x+12 | | 3cosx+5sinx-5=0 | | 4(2x-4)=8x+0 | | 4(2x-4)=8x+9 | | 4(2x-4)=8x+7 | | 4(2x-4)=8x+6 | | 4(2x-4)=8x+5 | | 4(2x-4)=8x+80 | | 4(2x-4)=8x+24 | | 4(2x-4)=8x+8 | | 4(2x-4)=8x+3 | | 4(2x-4)=8x+2 | | 4(2x-4)=8x+1 | | 3-2(x+4)=-17 | | 4(2x-4)=8x+4 | | 4(2x-4)=8x+32 | | 4(2x-4)=8x+ | | -6x=8x+5 |